Efficacy and safety of fixed-dose clindamycin phosphate 1.2%/adapalene 0.15%/benzoyl peroxide 3.1% gel in Hispanic participants with moderate-to-severe acne: a pooled analysis - Valerie D. Callender; Hilary Baldwin; Linda Stein Gold; Fran E. Cook-Bolden; Eric Guenin; Andrew F. Alexis (Journal of Dermatological Treatment)
Introduction Clindamycin phosphate 1.2%/adapalene 0.15%/benzoyl peroxide 3.1% (CAB) gel is the only fixed-dose, triple-combination approved for acne. In phase 2 and 3 studies, CAB demonstrated superior efficacy to vehicle and component dyads. This post hoc analysis examined efficacy/tolerability of CAB in 147 self-identified Hispanic/Latino participants (referred to as Hispanic).Methods Data were pooled from one phase 2 (NCT03170388) and two phase 3 (NCT04214652, NCT04214639) double-blind, 12-week studies. Eligible participants aged ≥9 years with moderate to severe acne were randomized to once-daily CAB or vehicle. Endpoints included ≥2-grade reduction from baseline in Evaluator’s Global Severity Score with clear/almost clear skin (treatment success) and inflammatory/noninflammatory lesion counts. Treatment-emergent adverse events (TEAEs) were assessed.Results At week 12, 56.2% of CAB-treated participants achieved treatment success vs 18.4% with vehicle (p < 0.001). Reductions in inflammatory/noninflammatory lesions were 77.1%/76.2% with CAB vs 56.4%/45.0% with vehicle, respectively (p < 0.001, all). CAB TEAE rates were similar to overall study populations (27.0% vs 24.6%-36.2%). Baseline hyperpigmentation scores decreased from 0.6 to 0.3 (1 = mild) at week 12 with CAB. CAB gel was efficacious, safe, and well tolerated in Hispanic participants. Limitations include lack of Fitzpatrick skin phototype and short study duration.Conclusions This study provides support for acne treatment with CAB in ethnically diverse populations.